2006
DOI: 10.1002/dev.20189
|View full text |Cite
|
Sign up to set email alerts
|

Influence of various early human–foal interferences on subsequent human–foal relationship

Abstract: Whereas the way animals perceive human contact has been particularly examined in pet animals, a small amount of investigations has been done in domestic ungulates. It was nevertheless assumed that, as pet animals, non-aggressive forms of tactile contact were as well rewarding or positive for these species, even though the features of intraspecific relationships in pet animals and domestic ungulates may be to some extent different. We test here the hypothesis that horses may not consider physical handling by hu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
34
0
3

Year Published

2007
2007
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(38 citation statements)
references
References 27 publications
(29 reference statements)
1
34
0
3
Order By: Relevance
“…3a). This is similar to findings in domestic horses, where FID was found to be lower in foals exposed to human presence in early life (Henry et al 2006). Second, FID was shorter in the western half of the island, where human activity is concentrated.…”
Section: Discussionsupporting
confidence: 88%
“…3a). This is similar to findings in domestic horses, where FID was found to be lower in foals exposed to human presence in early life (Henry et al 2006). Second, FID was shorter in the western half of the island, where human activity is concentrated.…”
Section: Discussionsupporting
confidence: 88%
“…This creates an insecure attachment to their mare that impairs their subsequent social relationships with conspecifics [8]. Forced contacts during the days following birth also has consequences on the perception a foal has of humans [9].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the behavior of the dam towards humans strongly influences the way their young respond to humans (horses: Henry et al, 2005;goats: Lyons et al, 1988) and consequently having a good relationship with the mother may simply improve the young' reactions to humans. Thus, Henry et al (2005) reported in horses that short periods of positive contacts with dams such as soft handling and hand-feeding during the first 5 days post-partum enhanced greatly foals' trainability at least until the age of 1 year, while direct handling of juveniles in the early postnatal period has either no effect or only short-term effects (Heird, Whitaker, Bell, Ramsey, & Lokey, 1986;Henry, Richard-Yris, & Hausberger, 2006;Lansade, Bertrand, & Bouissou, 2005;Simpson, 2002;Spier, Berger, Pusterla, Villarroel, & Pusterla, 2004;Williams et al, 2002Williams et al, , 2003.…”
Section: Introductionmentioning
confidence: 94%